PENINGKATAN KETERAMPILAN MENULIS PUISI DENGAN TEKNIK AKROSTIK BERBANTUAN MEDIA ETNO POCA (POETRY CARD) - Teguh Prastiyo; Sekar Dwi Ardianti; Rani Setiawaty (Jurnal Ilmiah Bina Edukasi, 2025)
This study aims to improve the poetry writing skills of Grade V students at SD Negeri 3 Rejosari Kudus through the use of acrostic techniques and ethno-poca media (poetry cards). The main problem faced by the students is their limited ability to write poetry, caused by a lack of vocabulary and difficulty in expressing ideas creatively. The acrostic technique was chosen to help students construct simple poetic structures, while the ethno-poca media was used to stimulate their creativity. The Classroom Action Research (PTK), conducted in two cycles, showed a significant improvement in students’ poetry writing skills (from 65.1 to 84.7). These results indicate that the combination of acrostic techniques and ethno-poca media is effective in helping students overcome difficulties in writing poetry.